4x+3-x=3(x-1)

Simple and best practice solution for 4x+3-x=3(x-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x+3-x=3(x-1) equation:


Simplifying
4x + 3 + -1x = 3(x + -1)

Reorder the terms:
3 + 4x + -1x = 3(x + -1)

Combine like terms: 4x + -1x = 3x
3 + 3x = 3(x + -1)

Reorder the terms:
3 + 3x = 3(-1 + x)
3 + 3x = (-1 * 3 + x * 3)
3 + 3x = (-3 + 3x)

Add '-3x' to each side of the equation.
3 + 3x + -3x = -3 + 3x + -3x

Combine like terms: 3x + -3x = 0
3 + 0 = -3 + 3x + -3x
3 = -3 + 3x + -3x

Combine like terms: 3x + -3x = 0
3 = -3 + 0
3 = -3

Solving
3 = -3

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 4x+3-x=39x-10 | | 1x/10=-2 | | 7x^2-34x-24=0 | | -8+-4+4= | | 114=.5h(10-9) | | 6x+130=11x-5 | | -3y-7=-28 | | 4x+4=4x+24 | | 103-x+2x=6x-7 | | 103-3+2x=6x-7 | | x(x+3x)=8(8+x+2) | | 2x+7x=10x-4 | | Y+2x+10=180 | | 2(n+5)=n+19 | | 5p+2=4-1 | | 7-7q=-15+-9q | | (4y^3-y-1)-(2y^2-3y+7)=0 | | 8y-2=-3(y-3) | | x*x+6x+9=-3x+1 | | 2+12x=123x | | 6-9x=36-13x | | 9st(7s-6t^2)= | | x+6x+9=-3x+1 | | 7(7+6)=x(x+4) | | 180=y+(5x+20) | | -12-15x=33 | | 6(v-9)=-2v-14 | | 9(3n-3)=(4n+8)+2 | | 0.3x+3=-2.3x+0.4 | | 7(x-1)+3(3-x)=5(1-x)-3(2x+1) | | 2(90-x)-6=124 | | 961=400+2x |

Equations solver categories